2018
DOI: 10.1007/s13197-018-3148-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory capacities of collagen peptides from milkfish (Chanos chanos) scales

Abstract: Milkfish (), which is resistant to water quality changes is the fourth largest aquaculture commodity. Abandoned wastes of fish scale and bones aggravate environmental pollution. In this study, the effect of collagen peptides isolated from milkfish scales (MSCP) by pepsin-soluble collagen method on cell viability was investigated. The antioxidant, anti-inflammatory, and DNA-protective activities of MSCP were also evaluated. Results revealed that more than 95% of viable cells were retained in human keratinocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Previous studies also reported that collagen subunits contain multiple host defense peptides [ 47 ]. What is more, some collagen-derived peptides have antioxidant and anti-inflammatory capacities [ 48 ], and even can suppress allergic responses [ 49 ]. In this present study, multiple collagen subunits aroused our attention since their mapping ratios are much higher compared with other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported that collagen subunits contain multiple host defense peptides [ 47 ]. What is more, some collagen-derived peptides have antioxidant and anti-inflammatory capacities [ 48 ], and even can suppress allergic responses [ 49 ]. In this present study, multiple collagen subunits aroused our attention since their mapping ratios are much higher compared with other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…() and Chen et al . (). They obtained higher anti‐oxidation active peptides firstly and found that the substance also possessed anti‐inflammatory ability.…”
Section: Resultsmentioning
confidence: 97%
“…Oxidative stress and inflammation are intimately connected. Reactive oxygen species and reactive nitrogen species (RNS) are ubiquitous in the body and regulate cellular function when at healthy levels [ 14 , 70 ]. However, oxidative stress plays a central role in chronic inflammation when dysregulated [ 80 ].…”
Section: Fish and Shellfish-derived Anti-inflammatory Protein Products: Properties And Mechanismsmentioning
confidence: 99%
“…A large portion of harvested marine resources currently go to waste [ 12 ]. Around 60–70% of initial fish and shellfish weight is considered byproduct, and is utilized in low-value applications or discarded outright [ 13 , 14 , 15 ]. SPB consists of heads, frames, skin, shells, and viscera, much of which contain high-quality nutrients, including lipids, minerals, and protein [ 16 ].…”
Section: Introductionmentioning
confidence: 99%